Assessing Implementation of Helping Babies Breathe Program Through Observing Immediate Care of Neonates at Time of Delivery - Martha Mayer; Nomvuyo Xhinti; Vuyiswa Dyavuza; Luzuko Bobotyana; Jeffrey Perlman; Sithembiso Velaphi (Frontiers Media S.A., 2022)
BackgroundTraining in neonatal resuscitation has been shown to reduce deaths related to intrapartum asphyxia. Helping Babies Breathe (HBB) is a simulation-based program focusing on training healthcare providers (HCPs) in immediate neonatal care including stimulation, initiating bag mask ventilation (BMV) in the absence of breathing by 1 min of life, and delayed (30-60 s after birth) umbilical cord clamping (DCC). Data on implementation of HBB posttraining are limited.ObjectiveTo determine time from birth to spontaneous breathing, cord clamping, and initiation of BMV in a setting where the majority of HCPs are HBB trained.MethodsTwo research nurses observed deliveries conducted in two referral hospitals. Timing included the onset of breathing, cord clamping, and initiation of BMV. Deliveries were grouped according to the mode of delivery.ResultsIn total, 496 neonates were observed; 410 (82.7%) neonates cried or had spontaneous breathing (median time 17 s) soon after birth, 25/86 (29%) of neonates not breathing responded to stimulation, 61 (12.3%) neonates required BMV, and 2 (0.4%) neonates required chest compression and/or adrenalin. Neonates delivered by cesarean section (CS) took longer to initiate first breath than those delivered vaginally (median time 19 vs. 14 s; p = 0.009). Complete data were available in 58/61 (95%) neonates receiving BMV, which was initiated in 54/58 (93%) cases within 60 s of life (the "Golden Minute"). Median time to cord clamping was 74 s, with 414 (83.5%) and 313 (63.0%) having cord clamped at ≥ 30 and ≥ 60 s, respectively. Factors associated with BMV were CS delivery [odds ratio (OR) 29.9; 95% CI 3.37-229], low birth weight (LBW) (birthweight < 2,500 g) (OR 2.47; 95% CI 1.93-5.91), and 1 min Apgar score < 7 (OR 149; 95% CI 49.3-5,021). DCC (≥ 60 s) was less likely following CS delivery (OR 0.14; 95% CI 0.02-0.99) and being LBW (OR 0.43; 95% CI 0.24-0.77).ConclusionApproximately 83% of neonates initiated spontaneous breathing soon after birth and 29% of neonates not breathing responded to physical stimulation. BMV was initiated within the Golden Minute in most neonates, but under two-thirds had DCC (≥60 s). HBB implementation followed guidelines, suggesting that knowledge and skills taught from HBB are retained and applied by HCP.